Perilaku Manajemen Keuangan Pada UMKM Sentra Kain Tenun Lurik Di Desa Tawang - Mutiara Meidiana; Anita Wijayanti; Agni Astungkara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the influence of financial knowledge, income, financial attitude, and personality on financial management behavior among owners of Micro, Small, and Medium Enterprises (MSMEs) in the village of Tawang, with a focus on the production of woven lurik fabric. All owners of MSMEs specializing in woven lurik fabric in the village of Tawang were included in this study, and the sampling method applied was saturation sampling. Primary data were obtained through the distribution of questionnaires to 86 respondents who are owners of MSMEs. Data was analyzed using multiple regression analysis methods. The results of the study indicate that financial knowledge has a positive and significant influence on financial management behavior among owners of MSMEs specializing in woven lurik fabric in the village of Tawang. Income has a positive and significant influence on financial management behavior among owners of MSMEs specializing in woven lurik fabric in the village of Tawang. Financial attitude has a positive and significant influence on financial management behavior among owners of MSMEs specializing in woven lurik fabric in the village of Tawang. Personality has a positive and significant influence on financial management behavior among owners of MSMEs specializing in woven lurik fabric in the village of Tawang. Keywords: Financial Knowledge; Income; Financial Attitude.